1967
DOI: 10.1161/01.res.20.2.272
|View full text |Cite
|
Sign up to set email alerts
|

Step Hypocapnia to Separate Arterial from Tissue Pco 2 in the Regulation of Cerebral Blood Flow

Abstract: The change in cerebral blood flow was determined after a step decrease in the Pco 2 of arterial blood from 40 to 25 mm Hg in awake man. Subjects monitored their own end-tidal Pcoo (infrared analyzer) and adjusted their voluntary ventilation to produce the step change, which they maintained for at least 1 hour. Cerebral blood flow relative to control was determined from the arterial-jugular venous oxygen saturation differences. After the step change, arterial Pco 2 fell in less than 30 sec to a plateau, cerebra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
76
1
1

Year Published

1968
1968
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(84 citation statements)
references
References 14 publications
6
76
1
1
Order By: Relevance
“…Pac02 has a major effect on cerebral-vascular resistance; flow increases with hypercarbia and decreases with hypocarbia (15,34); however, previous studies have shown that this effect is reduced or obliterated in the face of hypotension or circulatory failure (15,30). In our room-air breathing animals there was what Mchedlishvili (24) has called an antagonistic relationship between regulators of brain blood flow with hypotension and anemia tending to vasodilate and hypocarbia to vasoconstrict.…”
Section: Discussionmentioning
confidence: 74%
“…Pac02 has a major effect on cerebral-vascular resistance; flow increases with hypercarbia and decreases with hypocarbia (15,34); however, previous studies have shown that this effect is reduced or obliterated in the face of hypotension or circulatory failure (15,30). In our room-air breathing animals there was what Mchedlishvili (24) has called an antagonistic relationship between regulators of brain blood flow with hypotension and anemia tending to vasodilate and hypocarbia to vasoconstrict.…”
Section: Discussionmentioning
confidence: 74%
“…In healthy adults, CBF increases linearly by 2-4% per mmHg PaCO 2 within the range of 25-75 mmHg, making PaCO 2 the most potent physiologic cerebral vasodilator. The change in CBF occurs within seconds after PaCO 2 is increased or decreased, and complete equilibration occurs within 2 minutes [45]. There are no studies of age-related changes in CO 2 vasoreactivity in healthy awake children.…”
Section: Control Of the Cerebral Circulationmentioning
confidence: 99%
“…Alternatively, an increase in the pCO 2 tension in the cerebral tissues could be considered responsible for the flow increase but CO 2 induced changes of CBF are controlled by the arterial CO 2 level and not be the tissue level of CO 2 . 33 Finally, it has been speculated that the effect might occur via a direct inhibition of the carbonic anhydrase located in the brain tissue; large amounts of the enzyme has been demonstrated in the glial cells and in the choroid plexus, 34 and recently, in the endothelium of the capillaries throughout the brain tissue. 33 Following administration of Diamox, a gradual decline of pH in the brain tissue has been observed despite maintenance of a constant brain tissue p.COj.…”
Section: Mechanism Of Diamox Induced Cerebral Vasodilationmentioning
confidence: 99%
“…33 Finally, it has been speculated that the effect might occur via a direct inhibition of the carbonic anhydrase located in the brain tissue; large amounts of the enzyme has been demonstrated in the glial cells and in the choroid plexus, 34 and recently, in the endothelium of the capillaries throughout the brain tissue. 33 Following administration of Diamox, a gradual decline of pH in the brain tissue has been observed despite maintenance of a constant brain tissue p.COj. 36 - 37 The decrease in pH seems best explained by cerebral carbonic acidosis, i.e.…”
Section: Mechanism Of Diamox Induced Cerebral Vasodilationmentioning
confidence: 99%